DOES WORLD HERITAGE RECOGNITION DRIVE TOURISM? AN ANALYSIS OF SHIRAKAWA-G? VILLAGE THROUGH TRIPADVISOR REVIEWS - Eka Lestari, Nafitri; Wiweka, Kadek (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study explores how digital platforms shape heritage perception by analysing 898 TripAdvisor reviews of Shirakawa-go from 2010 to 2025. Using a mixed-methods approach, it combines sentiment classification and content analysis to understand how electronic word-of-mouth (e-WOM) conveys cultural significance. Reviews were categorised as Positive, Neutral, or Negative using RStudio. Findings show a predominantly positive sentiment, especially among couples (34.30%) and families (22.60%), with emotional peaks during winter months, reinforcing Shirakawa-go’s image as a snow-covered heritage village. However, recent reviews indicate declining satisfaction due to overtourism and commercialisation. This study explores how digital platforms shape heritage perception by analysing 898 TripAdvisor reviews of Shirakawa-go from 2010 to 2025. Using a mixed-methods approach, it combines sentiment classification and content analysis to understand how electronic word-of-mouth (e-WOM) conveys cultural significance. Reviews were categorised as Positive, Neutral, or Negative using RStudio. Findings show a predominantly positive sentiment, especially among couples (34.30%) and families (22.60%), with emotional peaks during winter months, reinforcing Shirakawa-go’s image as a snow-covered heritage village. However, recent reviews indicate declining satisfaction due to overtourism and commercialisation. A weak correlation (r ? 0.108) between sentiment and rating scores highlights the richer insights offered by textual analysis. Southeast Asian tourists expressed more positive emotions than European and domestic visitors, suggesting varying cultural responses to the site. The study is limited to English-language reviews from a single platform, which may exclude diverse perspectives. Future research should use multilingual, cross-platform data and triangulate findings with fieldwork or surveys. Overall, this research underscores the value of sentiment analysis for sustainable heritage tourism governance and calls for adaptive strategies to balance global tourist demand with local authenticity.